Follicle-like tertiary lymphoid structures: A potential biomarker for prognosis and immunotherapy response in patients with laryngeal squamous cell carcinoma - Liang, Haifeng; Zhang, Zhigang; Guan, Zhong; Zheng, Shibie; Lou, Jintao; Liu, Wei; Cai, Qian; Si, Yu (Frontiers in Immunology, 2023)
Background: The maturity and spatial distribution of tertiary lymphoid structures (TLSs) vary dynamically within and between cancers, leading to a controversial role in cancer. We aimed to develop a simple morphology-based approach to identify the maturity of TLSs in laryngeal squamous cell carcinoma and examine their clinically relevant functional role. Methods: TLSs were identified based on morphological features via hematoxylin and eosin (H&E) staining, and the accuracy was verified by multi-immunohistochemical analysis. The density, maturity, spatial distribution and prognostic value of TLSs were separately analyzed in two human laryngeal cancer cohorts. The TLS profile was linked to RNA-seq data from the TCGA database to perform bioinformatics analysis. Results: TLSs can be classified as early TLSs (E-TLSs), primary follicle-like TLSs (PFL-TLSs) and secondary follicle-like TLSs (SFL-TLSs). The three types of TLSs showed higher infiltration in the extratumoral region. XCL2 is a vital chemokine in the maturation and infiltration of TLSs. FL-TLS was an independent positive prognostic indicator in laryngeal cancer. The FL-TLS group had more abundant immune cell infiltration and a better response to immunotherapies than the non-FL-TLS group. Functional analysis showed that the non-FL-TLS group was enriched in tumor invasion, metastasis and immunosuppression pathways. Conclusion: The maturity of TLSs can be accurately classified by H&E staining. FL-TLS is a potential mediator of antitumor immunity in human laryngeal cancer.